2020
DOI: 10.5897/ajps2020.1977
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of combined strategies for the management of Asian soybean rust

Abstract: Asian soybean rust, if not well managed, can reduce grain yield up to 90%. Due to the severe damage caused by the disease, especially in Brazil, it is important to evaluate management strategies combined with fungicides, to minimize the losses. The aim of the work was to evaluate the effect of adopting different combined management strategies on the severity of soybean rust and its impact on the performance of the crop. Research was carried out at 2016/2017 and 2017/2018 growing seasons. Soybean cultivar NA 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, the sole use of resistant cultivars as a management choice has the same limitation as the use of fungicides: the selection of pathogen populations capable of overcoming the Rpp genes (Godoy et al, 2016a). Therefore, recent studies have investigated interaction effects of chemical and genetic control (Bahry et al, 2020; Sacon et al, 2020). A two‐year study (2016/17 to 2017/18) conducted in Paraná state found a significant reduction in SBR severity when combining fungicide treatment (AZOX + BENZ) with a resistant cultivar (TMG 7062; c.72%); slightly less reduction was obtained when fungicide was combined with the highly tolerant cultivar LG 60163 (c.64%) and less still with the susceptible cultivar NA 5909 (c.52.1%) (Bahry et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sole use of resistant cultivars as a management choice has the same limitation as the use of fungicides: the selection of pathogen populations capable of overcoming the Rpp genes (Godoy et al, 2016a). Therefore, recent studies have investigated interaction effects of chemical and genetic control (Bahry et al, 2020; Sacon et al, 2020). A two‐year study (2016/17 to 2017/18) conducted in Paraná state found a significant reduction in SBR severity when combining fungicide treatment (AZOX + BENZ) with a resistant cultivar (TMG 7062; c.72%); slightly less reduction was obtained when fungicide was combined with the highly tolerant cultivar LG 60163 (c.64%) and less still with the susceptible cultivar NA 5909 (c.52.1%) (Bahry et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recent studies have investigated interaction effects of chemical and genetic control (Bahry et al, 2020; Sacon et al, 2020). A two‐year study (2016/17 to 2017/18) conducted in Paraná state found a significant reduction in SBR severity when combining fungicide treatment (AZOX + BENZ) with a resistant cultivar (TMG 7062; c.72%); slightly less reduction was obtained when fungicide was combined with the highly tolerant cultivar LG 60163 (c.64%) and less still with the susceptible cultivar NA 5909 (c.52.1%) (Bahry et al, 2020). Sacon et al (2020) also reported higher SBR control applying AZOX + BENZ to resistant cultivars (>80%) compared to a susceptible one (c.56%) in field experiments conducted in northern Rio Grande do Sul state during 2016/17 and 2017/18 growing seasons.…”
Section: Discussionmentioning
confidence: 99%